Eksistensi Brand Rokok Lewat Strategi Stealth Marketing di Ajang Formula One - Chieka Serafino Adhista Lesilolo; Gregorius Genep Sukendro (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
This Following the implementation of the Framework Convention on Tobacco Control (FCTC), which imposed a global ban on tobacco sponsorship, cigarette companies have continued to maintain their brand presence in Formula One (F1). This study explains how such brand persistence has been sustained despite strict regulatory restrictions. Using a qualitative case study approach, data were collected through in-depth interviews with F1 fans, academics, and industry practitioners, supported by relevant literature and regulatory documents. The findings identify three main strategies. First, Visual Cues, such as consistent color schemes and abstract patterns, evoke brand recognition without displaying explicit logos. Second, Corporate Branding, exemplified by abstract identities such as Mission Winnow, constructs corporate narratives that distance the brand from direct tobacco promotion. Third, Brand Switching promotes alternative products that comply with local regulations while maintaining symbolic continuity with tobacco brands. This study also positions Surrogate Advertising as a manifestation of the brand-switching strategy. By developing a systematic typology of stealth marketing in F1, this research offers a new analytical framework for understanding marketing communication in highly regulated industries and emphasizes the importance of creative strategy in navigating legal constraints. Setelah Framework Convention on Tobacco Control (FCTC) memberlakukan larangan sponsor tembakau di seluruh dunia, sponsor rokok terus mempertahankan eksistensi merek mereka di Formula One (F1). Tujuan dari penelitian ini adalah untuk menjelaskan bagaimana ini terjadi. Data dikumpulkan melalui wawancara dengan penggemar F1, akademisi, dan praktisi industri menggunakan pendekatan studi kasus kualitatif. Hasil penelitian menunjukkan tiga strategi utama. Penelitian ini bertujuan untuk menyusun tipologi yang sistematis guna mengkategorikan strategi stealth marketing di ajang F1 sebuah upaya yang belum pernah dilakukan sebelumnya. Beberapa strategi yang dianalisis meliputi penggunaan Visual Cues (warna dan pola), Corporate Branding (dengan identitas abstrak seperti Mission Winnow), dan Brand Switching (dengan produk alternatif yang sesuai regulasi). Ketiganya memanfaatkan pendekatan kreatif guna mempertahankan visibilitas merek tanpa melanggar ketentuan yang berlaku. Selain itu, iklan atau sponsor pengganti (Surrogate Advertising) diposisikan dalam penelitian ini sebagai sebuah manifestasi dari strategi pergantian merek. Ini memberikan kerangka analisis baru untuk memahami fenomena komunikasi pemasaran di industri dengan regulasi ketat sekaligus menegaskan betapa pentingnya kreativitas dalam menghadapi pembatasan hukum.